Phylogenetic analysis of SARS‐CoV‐2 in the first few months since its emergence - Pereson, Matías J. (2020)
During the first months of SARS‐CoV‐2 evolution in a new host, contrasting hypotheses have been proposed about the way the virus has evolved and diversified worldwide. The aim of this study was to perform a comprehensive evolutionary analysis to describe the human outbreak and the evolutionary rate of different genomic regions of SARS‐CoV‐2.The molecular evolution in nine genomic regions of SARS‐CoV‐2 was analyzed using three different approaches: phylogenetic signal assessment, emergence of amino acid substitutions, and Bayesian evolutionary rate estimation in eight successive fortnights since the virus emergence.All observed phylogenetic signals were very low and tree topologies were in agreement with those signals. However, after four months of evolution, it was possible to identify regions revealing an incipient viral lineage formation despite the low phylogenetic signal, since fortnight 3. Finally, the SARS‐CoV‐2 evolutionary rate for regions nsp3 and S, the ones presenting greater variability, was estimated as 1.37 x 10‐3 and 2.19 x 10‐3 substitution/site/year, respectively.In conclusion, results from this work about the variable diversity of crucial viral regions and determination of the evolutionary rate are consequently decisive to understand essential features of viral emergence. In turn, findings may allow the first time characterization of the evolutionary rate of S protein, crucial for vaccine development.